Analisis Kedisiplinan Siswa ABK Ditinjau Dari Peran Teman Sebaya - Nurul Afidatul Ulya; Amelita Putri Rahmatia; Mega Ayu Mustika; Muhammad Nofan Zulfahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the discipline of students with special needs (ABK) with a focus on the role of peer influence. The discipline of ABK students is a crucial aspect of inclusive education development, and the role of peers is considered to have a significant impact on their discipline levels. The research method involves a literature review (library research). The results indicate that peer influence can either positively or negatively affect the discipline of ABK students. Peers providing support and understanding can enhance the motivation of ABK students to maintain discipline. On the other hand, peers who are less tolerant or demeaning can hinder the creation of a conducive educational environment. Certain factors such as understanding the special needs of students, teacher training, and family roles have also proven to influence the discipline of ABK students. The importance of integrating inclusive approaches into the school curriculum and the active involvement of peers in supporting ABK students is urgent. In conclusion, this research highlights the importance of understanding and enhancing the role of peers in shaping the discipline of ABK students. By considering factors such as understanding the special needs of students and the role of the family, more effective strategies can be developed to create an inclusive educational environment that supports the discipline of ABK students.